Оптимізація біотехнологічного процесу мікроклонального розмноження троянди ефіроолійної - Олійник, Ольга Олександрівна (НУБіП України, 2019)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук зі спеціальності 03.00.20 «Біотехнологія». Національний університет біоресурсів і природокористування України. Київ, 2019. Оптимізовано біотехнологічний процес мікроклонального розмноження рослин сортів троянди ефіроолійної, яка включає активацію росту меристем експлантата, прямий і непрямий морфогенез та дозволяє одержувати в стислі строки значну кількість рослин-регенерантів. Підібрано оптимальні концентрації регуляторів росту, мінеральних і вуглеводних компонентів живильного середовища для різних етапів та типів морфогенезу. Визначено оптимальні умови індукції калюсоутворення та показано морфогенетичну здатність отриманого калюсу. Підібрано умови ризогенезу, ґрунтові суміші та субстрати для поетапної процедури ступеневої адаптації рослин-регенерантів до умов відкритого ґрунту із приживлюваністю 95–98 % для сортів троянди ефіроолійної Лань, Лада та Радуга. Розроблено математичну модель циклічного біотехнологічного процесу мікроклонального розмноження троянди ефіроолійної, яка ґрунтується на базових фізіологічних ознаках модельних сортів і дозволяє оптимізувати технологію безперервного отримання якісного садивного матеріалу протягом тривалого часу
The thesis for a Candidate Degree of Agricultural Sciences, in specialty 03.00.20 Biotechnology. National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The Thesis presents theoretical justification according to biochemical, physiological and histochemical features of the Rosa damascena Mill. varieties influence on its morphogenetic potential in the in vitro culture and explores the possibility of using the method of microclonal propagation for getting high-quality planting material as an element of intensive technologies for introduction into production. The biotechnological process of planting material obtaining for highyielding varieties of rose essential oil cultivation has been optimized with the study of the morphogenetic, physiological and anatomical potential of their tissues and organs in vitro. The research materials were the model varieties Lan’, Lada and Raduga of Rosa damascena Mill. It has been shown that the activation of polyphenol synthesis occurs responding to traumatic damage of primary explants tissues under conditions of plant introduction into in vitro culture. The qualitative composition and the amount of polyphenols and condensed tannins the leaves of Rosa damascena Mill. were a marker for shoots as potential ability to the regeneration. It was found that in case if the concentration phenolic compounds in the leaves of primary explants were below 60 mg/g, the efficiency of plants introduction into in vitro culture increases significantly. The analysis of the donor material on the occurrence of the secondary metabolites made it possible to predict how the plant would adapt to the in vitro culture conditions. For Rosa damascena Mill. mass microclonal propagation by method of meristem activation Anderson medium, MS, QL, and WPM were used, using cytokinins and auxins: BAP, TDZ, NAA and IAA both individually and in combination. For microclonal propagation and getting plant-regenerant of Lan’ varieties were used MS+0.5 mg/l BAP+0.01 mg/l IAA, MS+0.1 mg/l TDZ and QL+0.5 mg/l BAP. The minimum multiplication factor was 1:8, the maximum ‒ 1:14, the length of shoots was from 3.0 to 5.0 cm. For the root system formation regenerating plants were subcultured on the hormonal nutrient media ½ MS, MS, and QL, root length 2.5–8.0 cm. The total duration of the cultivation cycle was 50 days. Microclonal propagation of Lada variety was performed on Anderson media+0.5 mg/l BAP; QL+2.0 mg/l BAP; WPM+1.5 mg/l BAP+0.1 mg/l NAA. The root system was formed on the medium ½ MS, but not developed good (2‒3 roots with a length of 1.0 to 2.0 cm), meanwhile the shoots height ranged from 2.0 to 3.5 cm. The minimum breeding factor is 1:2, the maximum is 1:4. The Lada variety had the longest cultivation cycle which lasted 80‒90 days. For the microclonal propagation of the Raduga variety, the explants were transferred to MS medium+0.1 mg/l TDZ. Under these cultivation conditions the minimum multiplication factor was 1:3, the maximum – 1:7, the shoots length ranged from 1.0 to 2.0 cm. Rhizogenesis occurred on the medium ½ MS and Anderson medium with a double Fe2++2.0 mg/l BAP, root length 1.0–1.5 cm. The cultivation cycle was 50–65 days. It was proved that in the zone of contact with living tissues oxybenzoic (vanillic, syringic, gallic) and oxycynnamic (p-coumaric, caffeic, ferulic) acids in the composition of the nutrient medium (conc. 1 mM/l) initiate callusogenesis. In the process of Rosa damascena Mill. model varieties cultivation a tendency of explants regenerative capacity increased rapidly with its subsequent decrease. This sortspecific feature makes it possible to consider the Lan’ variety are technologically attractive, since the intensity of regenerating plants production has remained high (13.5) for up to 24 months. In contrast, the high-phenolic varieties Raduga and Lada showed relatively low reproduction rates of 4.2 and 5.7, respectively. According to the results of propagation, we have developed a mathematical model of cyclic biotechnological process of Rosa damascena Mill. microclonal propagation, which is based on the basic physiological characteristics of model varieties and allows to optimize the technology of continuous production of quality planting material for a long time. The conditions of rhizogenesis, soil mixtures and substrates for the step-by-step procedure of stepwise adaptation of regenerated plants for the open ground conditions with a survival rate of 95–98 % for species of Rosa damascena Mill. Lan’, Lada and Raduga were selected
Keywords: троянда ефіроолійна; мікроклональне розмноження; in vitro; рослини-регенеранти; прямий морфогенез; калюс; вторинні метаболіти; фенольні сполуки; ex situ; microclonal propagation; regenerant plants; direct morphogenesis; callus